Mapping the current landscape of locoregional therapy de-escalation trials in early breast cancer: a systematic review - Alan D. McCrorie; Hilary Stobart; David Dodwell; Stuart A. McIntosh; Shelley Potter (npj Breast Cancer)
Abstract A systematic review undertaken to map the current landscape of locoregional de-escalation trials to inform future research. Online databases and trial registries were searched to identify ongoing, recently completed or published studies de-escalating surgery or radiotherapy in patients with early breast cancer. 97 trials evaluated de-escalation of surgery or radiotherapy in up to 94,866 participants. Surgery studies more commonly evaluated treatment omission/reduction after neoadjuvant systemic therapy (NST) and de-escalation of nodal treatment. Radiotherapy studies were more frequently biomarker stratified. Patients were rarely involved in study design. Research questions focused on response-adjusted treatment after NST and omission/reduction of locoregional therapy in patients with low- or intermediate-risk disease. Significant duplication was identified with multiple studies addressing similar questions. This systematic review demonstrates that the current de-escalation portfolio is inefficient, lacks patient focus and needs improvement. An internationally collaborative approach using innovative study designs and patient partnership will be essential to address this.